2020
DOI: 10.21873/anticanres.14502
|View full text |Cite
|
Sign up to set email alerts
|

Ephemeranthol A Suppresses Epithelial to Mesenchymal Transition and FAK-Akt Signaling in Lung Cancer Cells

Abstract: Background/Aim: Epithelial to mesenchymal transition (EMT) is a cellular process that facilitates cancer metastasis. Therefore, therapeutic approaches that target EMT have garnered increasing attention. The present study aimed to examine the in vitro effects of ephemeranthol A on cell death, migration, and EMT of lung cancer cells. Materials and Methods: Ephemeranthol A was isolated from Dendrobium infundibulum. Non-small cell lung cancer cells H460 were treated with ephemeranthol A and apoptosis was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Petpiroon et al reported that phoyunnanin E inhibited the motility of lung cancer cells via the suppression of EMT and cancer metastasis-related integrins, such as integrin αv and integrin β3 [23]. Our previous results showed that ephemeranthol A, a natural compound isolated from D. infundibulum, also exhibited inhibitory effects on migration and EMT via suppression of the FAK-AKT signaling pathway [24]. Similarly, batatasin III was reported to have an inhibitory effect on cancer migration and invasion by suppressing EMT [25].…”
Section: Discussionmentioning
confidence: 88%
“…Petpiroon et al reported that phoyunnanin E inhibited the motility of lung cancer cells via the suppression of EMT and cancer metastasis-related integrins, such as integrin αv and integrin β3 [23]. Our previous results showed that ephemeranthol A, a natural compound isolated from D. infundibulum, also exhibited inhibitory effects on migration and EMT via suppression of the FAK-AKT signaling pathway [24]. Similarly, batatasin III was reported to have an inhibitory effect on cancer migration and invasion by suppressing EMT [25].…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, p-FAK (phosphorylated at Tyr397), p-Akt (phosphorylated at Ser473), and Cdc42 were found to be significantly reduced in response to non-toxic dose of norcycloartocarpin in A549, H460, H23, and H292 cells ( Fig 4 ). Previous reports indicated that phosphorylated FAK and Akt have been reported to serve a significant role in the regulation of cell proliferation, survival, adhesion, and migration [ 74 76 ]. Thus, we suggested that the reduction of phosphorylated FAK and Akt may mediate the inhibitory effect of norcycloartocarpin on cell migration and EMT of lung cancer cells via the inhibition of the FAK/Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Cypripedin isolated from Dendrobium densiflorum is effective against lung cancer by activating caspase-3 and downregulating the antiapoptotic proteins Bcl-2 and Bcl-xL in cells [167]. Denbinobin also isolated from Dendrobium and Ephemerantha also promotes caspase-3 activity in lung adenocarcinoma cells [168,169] and a polysaccharide extracted from Anoectochilus roxburghii inhibits in this way the growth and proliferation of human prostate cancer (PC-3) cells [138].…”
Section: The Anticancer Effect-potential Mechanism Of Action and Acti...mentioning
confidence: 99%